Policy Evaluation of Non-Cash Food Assistance Program Distribution in Tarogong District Kidul Garut Regency - Raesalat, Riksa; Purnawan, Ade; Kania, Ikeu; Miftahudin, Salfa (ann4publisher@gmail.com, 2024)
The Non-Cash Food Assistance Program (BPNT) is a program to provide non-cash food assistance from the government which is given to KPM every month through banking mechanisms. The existence of this program is because in Covid-19, the community's economy is very difficult to make a living due to government policies that implement lockdowns regularly in every region of Indonesia, especially Garut Regency which is the focus of research. The method applied is a descriptive qualitative method using the location of the researcher is Tarogong Kidul District and Villages in the Tarogong Kidul area, Garut Regency. This research aims to create poor food security in Garut Regency. The Policy Evaluation Theory used in this study uses the theory of William N Dunn. The results of this study show that BPNT distribution has been carried out well according to existing procedures, although there are still obstacles in BPNT distribution in data collection. This is because some villages in the Tarogong Kidul District area still have not updated the integrated social welfare data (DTKS) that will be inputted by the Garut Regency Social Office.